PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJAKARYAWAN PADA PT SUPRA CITRA INTITAMA BEKASI - Sawalman Zalukhu; Akhmar Barsah (Jurnal Menara, 2025)
This study examines the influence of organizational culture and work motivation on employee performance at PT Supra Citra Intitama Bekasi. The research employed a quantitative approach with an associative design, utilizing census sampling technique involving 60 permanent employees. Data collection was conducted through questionnaires using a 5-point Likert scale, with analysis performed using multiple linear regression, correlation analysis, and hypothesis testing. The findings reveal that organizational culture has a positive and significant effect on employee performance with a correlation coefficient of 0.783 (strong category) and contributes 78.3% to performance variance. Work motivation demonstrates a stronger influence with a correlation coefficient of 0.879 (very strong category) and contributes 87.9% to employee performance. Simultaneously, both variables exhibit a very strong effect on employee performance with a combined contribution of 88.5%, indicating optimal synergistic effects. Despite both organizational culture (mean score 2.80) and work motivation (mean score 2.76) being categorized as poor, their significant impact on performance suggests substantial improvement potential through strategic interventions. These findings provide practical implications for management to prioritize integrated strategies that synergize organizational culture enhancement through innovation and communication openness with work motivation improvement through comprehensive compensation systems, job security, and recognition programs to optimize employee performance in competitive business environments.